Comparative Analysis of Adelphocoris suturalis Jakovlev (Hemiptera: Miridae) Immune Responses to Fungal and Bacterial Pathogens - Ma, Meiqi; Guo, Libin; Tu, Chengjie; Wang, Aoli; Xu, Letian; Luo, Jing (Frontiers in Physiology, 2021)
The wide-spread culture of transgenic Bt cotton to resist infamous cotton bollworms has reduced the adoption of broad-spectrum insecticides to a large extent. Consequently, the non-targeted insect Adelphocoris suturalis Jakovlev has become a major pest of cotton in China. Entomopathogenic microbes show a promising future to control this pest, but A. suturalis innate immune responses to these pathogens are poorly understood. Here, we used the entomopathogenic fungus B. bassiana and the Gram-negative pathogenic bacteria E. cloacae to infect A. suturalis nymphs, followed by high throughput RNA-seq to analyze the immune transcriptomes of A. suturalis in response to the two pathogens. A total of 150 immunity-related genes were identified, including pattern recognition receptors, extracellular signal modulators, signal pathways (Toll, IMD, JNK, JAK/STAT), and response effectors. Further quantitative real-time PCR analysis demonstrated that B. bassiana and E. cloacae were recognized by different receptors (GNBP and PGRP, respectively); activated Toll pathway and IMD pathway respectively; and both induced expression of the effector gene Defensin. However, melanization is suppressed in B. bassiana-infected nymphs. Collectively, this study provided a transcriptomic snapshot of the A. suturalis immune system, and at genetic level, gained multifaceted insights of the immune response to fungal and Gram-negative bacterial pathogens. Ultimately this work will pioneer the study of molecular mechanisms underlying immune interactions between A. suturalis and its pathogens, and assist the development of novel mitigation strategies to control this pest.